Effects of kenaf fiber bleaching and waste cooking oil on properties of PLA/kenaf biocomposite - Abdul Razak, Nur Inani (2015)
Biocomposite made from poly(lactic acid) (PLA) and kenaf fiber offers a totally biodegradable and cost effective material. Owing to poor fiber-matrix adhesion and unattractive colour appearance, kenaf fiber was treated by bleaching method. The bleaching treatment was conducted in a solution of hydrogen peroxide at pH 11, 80 °C for 60 minutes. In this study, the biocomposites were prepared via melt blending technique using Haake Polydrive. Due to the bleaching treatment, the amorphous components such as hemicellulose and lignin were partially removed from the bleached kenaf fiber, which resulting good colour appearance of fiber, improvement in thermal stability and increase of crystallinity. The biocomposites that produced from the combination of bleached kenaf fiber and PLA were considerably brighter than PLA/unbleached kenaf fiber biocomposites. However, the elongation at break of PLA/bleached kenaf fiber biocomposite was lower than PLA, indicating that the kenaf fiber bleaching treatment did not improve the flexibility of biocomposite. Therefore, waste cooking oil (WCO) was tested as a plasticizer for the biocomposites in order to alter this drawback. The simultaneous effects of kenaf fiber bleaching and WCO on PLA/kenaf fiber biocomposites were investigated with respect to mechanical properties, thermal properties, morphology, biodegradability and water absorption. As compared to PLA/unbleached kenaf fiber biocomposites, good physical interactions between bleached kenaf fiber and plasticized matrix resulted in the increase of elongation at break, tensile strength, flexural strength, impact strength and thermal stability. Because of the plasticization effect, the addition of WCO reduced the tensile modulus, flexural modulus and glass transition temperature. The observation via scanning electron microscope (SEM) on the fractured tensile surface showed close adhesion between bleached kenaf fiber and plasticized matrix. Consequently, it was found that the water absorption and decomposition of biocomposites in soil decreased because the close gap at fiber-matrix interfaces reduced the penetration of water and microorganisms into the biocomposites.